Mercury in Neotropical birds: a synthesis and prospectus on 13 years of exposure data - Christopher J. Sayers; David C. Evers; Viviana Ruiz-Gutierrez; Evan Adams; Claudia M. Vega; Jessica N. Pisconte; Vania Tejeda; Kevin Regan; Oksana P. Lane; Abidas A. Ash; Reynold Cal; Stevan Reneau; et al. (Ecotoxicology, 2023)
Environmental mercury (Hg) contamination of the global tropics outpaces our understanding of its consequences for biodiversity. Knowledge gaps of pollution exposure could obscure conservation threats in the Neotropics: a region that supports over half of the world’s species, but faces ongoing land-use change and Hg emission via artisanal and small-scale gold mining (ASGM). Due to their global distribution and sensitivity to pollution, birds provide a valuable opportunity as bioindicators to assess how accelerating Hg emissions impact an ecosystem’s ability to support biodiversity, and ultimately, global health. We present the largest database on Neotropical bird Hg concentrations ( n = 2316) and establish exposure baselines for 322 bird species spanning nine countries across Central America, South America, and the West Indies. Patterns of avian Hg exposure in the Neotropics broadly align with those in temperate regions: consistent bioaccumulation across functional groups and high spatiotemporal variation. Bird species occupying higher trophic positions and aquatic habitats exhibited elevated Hg concentrations that have been previously associated with reductions in reproductive success. Notably, bird Hg concentrations were over four times higher at sites impacted by ASGM activities and differed by season for certain trophic niches. We developed this synthesis via a collaborative research network, the Tropical Research for Avian Conservation and Ecotoxicology (TRACE) Initiative, which exemplifies inclusive, equitable, and international data-sharing. While our findings signal an urgent need to assess sampling biases, mechanisms, and consequences of Hg exposure to tropical avian communities, the TRACE Initiative provides a meaningful framework to achieve such goals. Ultimately, our collective efforts support and inform local, scientific, and government entities, including Parties of the United Nations Minamata Convention on Mercury, as we continue working together to understand how Hg pollution impacts biodiversity conservation, ecosystem function, and public health in the tropics.